When do firms evaluate further training measures? - Baechmann, Ann-Christin; Abraham, Martin; Huber, Martina (International Journal of Manpower, 2019)
Purpose Increased investments in employee further training have resulted in a growing interest in ensuring and improving the quality of these measures. However, little is known about the operational decision to initiate an evaluation of further training. Therefore, the purpose of this paper is to investigate under which circumstances firms decide to evaluate training measures.
CRIS-Team WoS Importer:2019-04-16